Implementasi Project Based Learning (PjBL) Untuk Meningkatkan Kreativitas Peserta Didik Pada Mata Pelajaran Pendidikan Pancasila - Faizah, Zima Aulia; Chotimah, Umi (Universitas Muhammadiyah Ponorogo, 2026)
Learning in the subject of Pancasila Education at the present time requires students’ creativity in its implementation. One approach that can be applied to enhance students’ creativity is the Project-Based Learning (PjBL) model. This study aims to identify the effect of implementing the PjBL model on improving students’ creativity in the Pancasila Education subject at SMPN 1 Indralaya, particularly in Grade VII. The method used in this research is a quantitative approach with a quasi-experimental research design, specifically the non-equivalent control group design. The sample was selected using a non-probability method with purposive sampling, resulting in Class VII F as the experimental group with a total of 37 students, and Class VII G as the control group with the same number of students. Data collection techniques included tests, observations, and documentation, while data analysis methods involved normality tests, homogeneity tests, and hypothesis testing using the independent sample t-test. The results showed that the significance value was 0.003 < 0.05. Based on these findings, it can be concluded that there is a significant effect of implementing the PjBL model on enhancing students’ creativity in the subject of Pancasila Education at SMPN 1 Indralaya.